How the international humanitarian system supports government disaster response : guide for governments 2011 (REDLAC AnconPA, 2011)
Promotes basic knowledge of the international humanitarian system in national authorities in Latin America and the Caribbean in order to facilitate, when needed, the rapid mobilisation of assistance to help governments respond to the immediate needs of those most affected by natural disasters.
Keywords: HUMANITARIAN ASSISTANCE